WÅ‚odzimierz Sobkowiak. Phonetics of EFL Dictionary Definitions - de Schryver, Gilles-Maurice (Lexikos, 2007)
Just as book reviews are written for a variety of reasons, the reviews them-selves serve various purposes. Chief among the latter is probably one’s wish to know whether or not one should actually read the book under review. Let me therefore state upfront that, yes, this work should be on every (meta)lexico-grapher’s bookshelf, where it should only be allowed to gather dust once it has been carefully studied and its contents seriously pondered. When Sobkowiak himself claimed, on p. 14 of the work under review, that "every lexicographer should read this book", I was sceptical, but after having read through the entire text twice, I have to conclude that he is indeed correct.